2013
DOI: 10.1098/rspb.2013.1390
|View full text |Cite
|
Sign up to set email alerts
|

Bone-eating worms from the Antarctic: the contrasting fate of whale and wood remains on the Southern Ocean seafloor

Abstract: We report the results from the first experimental study of the fate of whale and wood remains on the Antarctic seafloor. Using a baited free-vehicle lander design, we show that whale-falls in the Antarctic are heavily infested by at least two new species of bone-eating worm, Osedax antarcticus sp. nov. and Osedax deceptionensis sp. nov. In stark contrast, wood remains are remarkably well preserved with the absence of typical wood-eating fauna such as the xylophagainid bivalves. The combined whale-fall and wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 39 publications
2
72
1
Order By: Relevance
“…This adds to the growing evidence that the Cretaceous was a key period for the evolution of modern chemosynthetic communities [1,24]. The evolution of Osedax has been viewed as an extreme adaptation to deep-sea environments as most species of Osedax have been discovered at bathyal depths, but shallower species have been documented from the Antarctic, Japan and the Northeast Atlantic [25]. Osedax mucofloris has been found at multiple sites from 30 to 125 m depth and is the only species known from the North Atlantic [15].…”
Section: Discussionmentioning
confidence: 98%
“…This adds to the growing evidence that the Cretaceous was a key period for the evolution of modern chemosynthetic communities [1,24]. The evolution of Osedax has been viewed as an extreme adaptation to deep-sea environments as most species of Osedax have been discovered at bathyal depths, but shallower species have been documented from the Antarctic, Japan and the Northeast Atlantic [25]. Osedax mucofloris has been found at multiple sites from 30 to 125 m depth and is the only species known from the North Atlantic [15].…”
Section: Discussionmentioning
confidence: 98%
“…There is only evidence for two other Osedax species occurring across a range of depths (Tables 3, 5). Osedax antarcticus has been found from 546-1446 meters (Glover et al 2013;Amon et al 2014), and O. deceptionensis is known from 10-156 meters (Taboada et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…For example, foraminifera studies have identified how the ocean temperature has changed over the last 125 000 years (Labeyrie et al, 1987). In a similar way, deep-sea environmental conditions are suitable for exceptional preservation of historical cultural artifacts, including ancient Black Sea shipwrecks (Ballard et al, 2001) and potentially much more recent artifacts from polar expeditions (Shackleton's Endurance, Glover et al, 2013).…”
Section: Cultural Servicesmentioning
confidence: 99%